How Standardized Is Accounting? - Madsen, Paul E (The Accounting Review, 2011)
ABSTRACT There is disagreement in the accounting community about what level of standardization would be efficient for accounting. Many of the known costs and benefits of standardization have gone unmeasured and, as a result, there have been no efforts to quantitatively identify an efficient level of accounting standardization. Without guidance from researchers, the level of accounting standardization is set according to the intuition of standard-setters. Using data on a large cross-section of occupations, I provide evidence that the level of standardization in financial reporting occupations is far higher than would be expected given their characteristics. I then show with time-series data that the breadth of professional accounting discourse declined during the late 20th century, coincident with increases in the output of standard-setters. A lower quality discourse is one of many possible consequences of inefficient standardization. Data Availability: Occupations data in the O*NET, Career One Stop, and Occupational Employment Statistics (OES) databases are available from the U.S. Department of Labor. Data from the General Social Survey (GSS) are available from the National Opinion Research Center (NORC) at The University of Chicago. Contact the author for the data collected from the Accountants' Handbook.